1998
DOI: 10.1016/s0002-9440(10)65689-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression Status of p16 Protein Is Associated with Human Papillomavirus Oncogenic Potential in Cervical and Genital Lesions

Abstract: The p16 protein (p16) is a cyclin-dependent kinase (CDK) inhibitor that decelerates the cell cycle by in-Many studies have shown that human papillomavirus (HPV) infection plays an important role in cervical carcinogenesis.1 In fact, HPV infection has been detected in almost all preneoplastic and neoplastic lesions of the cervix. Recent extensive studies have revealed the existence of more than 70 subtypes of HPV, of which approximately 20 can infect the cervical epithelium and give rise to various lesions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

32
450
5
25

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 527 publications
(512 citation statements)
references
References 33 publications
32
450
5
25
Order By: Relevance
“…45 However, in tumours with HPV infection, accumulation of p16 INK4A is a well-known event in response to RB inactivation by viral E7 protein. 46 We detected a lack of p16 INK4A nuclear and cytoplasmic expression in our penile verrucous carcinoma series in 93% (14/15) and 87% (13/15) of cases, respectively. Ferreux et al 47 found at least three alternative mechanisms targeting the p16 INK4A /cyclin D/RB pathway in penile carcinoma.…”
Section: Discussionmentioning
confidence: 51%
“…45 However, in tumours with HPV infection, accumulation of p16 INK4A is a well-known event in response to RB inactivation by viral E7 protein. 46 We detected a lack of p16 INK4A nuclear and cytoplasmic expression in our penile verrucous carcinoma series in 93% (14/15) and 87% (13/15) of cases, respectively. Ferreux et al 47 found at least three alternative mechanisms targeting the p16 INK4A /cyclin D/RB pathway in penile carcinoma.…”
Section: Discussionmentioning
confidence: 51%
“…Several studies using p16 have corroborated the above results and confirmed that nearly all high-grade CIN lesions and invasive carcinomas immunohistochemically express very high levels of p16, whereas normal and hyperplastic cervical epithelia usually do not express p16. 21,30,31 Moreover, these findings also have been confirmed in cytologic specimens using liquid-based Pap smears. However, to our knowledge, there are no systematic reports published to date examining immunohistochemical p16 expression and HPV status in both cytology and tissue samples obtained simultaneously from the same patient.…”
Section: Discussionmentioning
confidence: 58%
“…In 1998, Sano et al clearly demonstrated the overexpression of p16 in CIN lesions and nearly all cervical carcinomas. 16,30 Moreover, because p16 overexpression is observed in many CIN lesions with highrisk and intermediate-risk HPV infections, p16 is be- lieved to be a suitable biomarker for screening CIN lesions and cervical carcinoma during routine pathologic diagnosis. Several studies using p16 have corroborated the above results and confirmed that nearly all high-grade CIN lesions and invasive carcinomas immunohistochemically express very high levels of p16, whereas normal and hyperplastic cervical epithelia usually do not express p16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,7,37 The upregulation of p16 INK4A results from inactivation of pRb by the HPV-E7 oncoprotein, or alternatively through E7-mediated epigenetic induction of KDM6B, subsequently leading to activation of the p16 INK4A gene. 6,16 Although several studies have reported a high interobserver conformity in the evaluation of p16 INK4A immunostaining patterns, 4,14,18,19,42 others have indicated limitations in this procedure. The immunohistochemical p16 INK4A staining procedure is subject to variations in the protocol and to difficulties in the interpretation of the staining patterns as a result of different scoring criteria.…”
Section: Discussionmentioning
confidence: 99%